Updated checklist of fishes at Cabo Pulmo reef, Gulf of California, Mexico - Ayala-Bocos, Arturo (2018)
Cabo Pulmo National Park is among the most successful protected areas in the Eastern Pacific Ocean and harbors the most northern coral reef in that region. The objective of this paper was to update the latest published checklist of fishes at the park. Over 500 censuses were conducted between 2004 and 2017. In addition, an extensive bibliographic review was conducted of records published on the local ichthyofauna from 2001 to 2017. As a result, 69 new records of reef fish species were added to the Cabo Pulmo reef checklist, corresponding to 24 orders, 35 families and 51 genera. With these additions, the current updated checklist consists of 302 species, corresponding to 194 genera, 74 families, and 24 orders.